Preparation method of three-dimensional gamma-Fe2O3 nano material and application thereof - ZHANG QUANSHENG; HUO MENGFEI; REN ZHEN; ZHANG DAOMING; ZHANG LIHENG; CHENG SUZHEN (2016)
The invention discloses a preparation method of a three-dimensional gamma-Fe2O3 nano material and application thereof. The method includes: firstly adding an iron source into an organic solvent, conducting heating to reach a reflux state, then depositing an electrolyte solution orderly on a conductive substrate with a 3D structure, and conducting annealing treatment to prepare the gamma-Fe2O3 material. The material provided by the invention has a three-dimensional micrometer or nanometer porous structure. Electrochemical testing proves that the three-dimensional gamma-Fe2O3 nano material has excellent circulation and rate capability, and can be used as the electrode material of a super capacitor. The method provided by the invention has the characteristics of simple preparation process, low cost and low equipment requirement. The obtained material has the advantages of uniform deposit and micropore structure, controllable deposition thickness, and good product uniformity. 本发明公开了种三维γ-FeO纳米材料的制备方法及其应用。本发明首先向有机溶